The Determination of the Type of Child Development Disorders with the Dempster Shafer Method: Penentuan Tipe Gangguan Perkembangan Anak dengan Metode Dempster Shafer - Checi Lia Sari Sinulingga; Fuzy Yustika Manik; Tioria Pasaribu (Cattleya Darmaya Fortuna, 2023)
Children are the most beautiful gift for parents. These gifts sometimes have shortcomings or many of them experience disorders during their development. There are various kinds of developmental disorders suffered by children including: autism, ADHD, ADD, speech delay, asperger syndrome, and taurette syndrome. In Indonesia, 5% of the school-age population to some degree in experiencing developmental disorders, one of which is Hyperactivity Disorder. Hyperactivity disorder is more common among boys than girls, estimated at 2-4% for girls, and 6-9% for boys aged 6-12 years. One of the real challenges today is the high cost of conducting a medical examination. So many children are not brought by their parents to undergo examination due to limited costs. In addition to financing, the lack of experts or specialists in the field of child health is also a factor in parents being reluctant to check their children. The situation is a lot in the area, especially those far from the city center. In this study, the Dempster Shafer method will provide an initial diagnosis and classification of types of child development disorders into several classifications such as in the case of Hyperactivity Disorder, with categories of Hyperactivity, Inpulsive, and Inatensi. Based on the results of manual calculations using Dempster Shafer, a value presentation of 0.6 leads to invasive disease.